Socioeconomic factors influencing chicken meat production in Peru during the 2016–2020 period - Zuazo, José (2025)
The objective of this study was to analyze the relationship between population growth and micro- and macroeconomic factors influencing chicken meat production in Peru during the 2016–2020 period. An observational, descriptive, cross-sectional, and correlational research design was employed. The calculation of the Pearson correlation coefficients revealed strong, positive, and statistically significant linear relationships between chicken meat production and demographic variables (population growth: r = 0.9951; p = 0.0004), microeconomic variables (average annual household income: r = 0.8824; p = 0.0475; national consumption of hard yellow maize: r = 0.9442; p = 0.0157), and macroeconomic variables (import of hard yellow maize: r = 0.9472; p = 0.0145; gross domestic product: r = 0.9106; p = 0.0316). A significant negative linear relationship was also observed with soybean meal imports (r = –0.9064; p = 0.0339). The coefficient of determination indicated that these variables explain more than 82% of the variance in national production, reflecting a model with high explanatory power. It is concluded that the Peruvian poultry sector shows a trend of expansion, influenced by economic and demographic factors, as well as by the high acceptance of chicken among the population due to its accessibility, low cost, and culinary versatility. Nevertheless, structural vulnerability is noted in relation to internal factors—such as inflation—and external factors—such as an increase in international prices of key inputs. Finally, pending challenges are highlighted, aimed at integrating the sub-sectors of the production chain, modernizing the regulatory framework, and promoting public-private investment to strengthen the competitiveness of the national poultry sector.